Performance of retrofitted reinforced concrete beam with anchored carbon fiber reinforced polymer rods and concrete jacket under increasing repetitive bending - Al-Khateeb, Mahmood Yahya Hasan (2021)
Recently, the applications of Fiber Reinforced Polymer (FRP) composite materials have shown a significant growth in the strengthening and retrofitting of Reinforced Concrete (RC) structural beams in terms of extending their effective life duration, reducing deformation, and increasing load capacity. However, Externally Bonded (EB) and Near Surface Mounted (NSM) systems are the most well-known techniques that have been applied lately to strengthen beams. But these approaches have some drawbacks, including poor performance against fire, degradation of the polymer matrix under Ultraviolet (UV) radiation, low compatibility between the epoxy matrix and the concrete substrate, thermal incompatibility between the FRP composites and concrete substrates, and unmatured de-bonding phenomena, which greatly reduce the effects of strengthening systems. Hence, RC structures strengthened with FRP material failed at loads less than their ultimate capacity, especially when subjected to repeated loading. This is because repeated loading leads to progressive degradation of the bond at the FRP-adhesive- concrete interfaces and results in failure at bond stresses lower than the ultimate monotonic bond stress. Therefore, the main goal of this research is to propose a new RC beam strengthening technique to overcome the shortcomings of existing methods and prove its functionality and effectiveness under incremental repetitive bending. The proposed system consists of Carbon Fiber Reinforced Polymer (CFRP) rods attached to the beam’s bottom surfaces (at the tensile zone). The rods are fixed to the beams using a Mechanical Anchorage System (MAS), which mainly consists of clipping steel plates and expansion anchor bolts. A new cast-in-situ concrete jacket covers the MASs and the CFRP rods. An epoxy composite layer is utilized on the bottom surface of the existing beams to avoid premature de-bonding between the old beam concrete and the new cast jacketing concrete to ensure that the strengthening system functions properly. A full-scale experimental test has been conducted on eight beams strengthened using the new proposed system. The eight beams were cast for this purpose and subjected to incremental repetitive bending load until failure following the four-point standard test setup. To examine the influence of each component of the proposed system, each beam with a specific setting is considered. Initial cracking, yielding, and ultimate loads, crack pattern, and mode of failure were recorded and discussed to evaluate the performance of the strengthened beams. Numerical simulation models have been developed using finite element software to evaluate the current proposed strengthened system performance and investigate more design parameters. In addition, an analytical calculation was applied to assess the ability of current design guidelines and codes to predicate the behavior of the proposed system in terms of elastic and plastic deflection, moment-curvature curve, ultimate load, and crack pattern. The experimental testing results indicated that the new proposed system effectively prevents premature de-bonding phenome, which led to an increase in the ultimate load capacity ranging between 87% and 120%. Furthermore, excellent bonding in the contact region between the old, existing concrete surface and the fresh concrete jacketing was observed along with the test until the failure. Numerical simulation results also showed excellent agreement with the experimental ones in terms of load–deflection, maximum load capacity, and mode of failure. Besides, FE output has confirmed the MAS’s contribution to bonding and capacity performance and the limited effect of the thickness and grade of concrete jacketing. The results of the analytical calculation showed that the current formula predicts the response of the tested beam specimens with reasonable accuracy. Overall, the results demonstrated that the new proposed prototype could be a promising replacement for the current strengthening system by providing accepted strengthening performance and durability.